2017
DOI: 10.1007/s00003-017-1129-6
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin risk management in commercial groundnut products in Malawi (Sub-Saharan Africa): a call for a more socially responsible industry

Abstract: This study was performed as a follow-up to a study from 2013, to assess the impact of management interventions on aflatoxin incidence and levels in commercial groundnut products in Malawi. Sixtyseven samples of commercial groundnut products were analyzed for aflatoxin using a fluorometric method. Total aflatoxin levels ranged from 1.5 to 1200 lg/kg in raw groundnuts and 83-820 lg/kg in groundnut flour from vendors. In branded groundnut flour and peanut butter from supermarkets, aflatoxin levels ranged from 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In the African context, establishment of standards and enforcement of regulations is currently driven by trade and the desire to comply with export regulations [48]. The inability to enforce even the single, existing aflatoxin standard renders it useless and gives the false impression of controlling the situation [49]. Sirma et al suggested that aflatoxin standards for food and feeds would be more effective if the context of local conditions were considered, such as typical crops used as ingredients, capacity to enforce regulations, differentiated aflatoxin contamination levels in food and feeds, regional standards, and societal concerns (food and nutrition security) [50].…”
Section: Discussionmentioning
confidence: 99%
“…In the African context, establishment of standards and enforcement of regulations is currently driven by trade and the desire to comply with export regulations [48]. The inability to enforce even the single, existing aflatoxin standard renders it useless and gives the false impression of controlling the situation [49]. Sirma et al suggested that aflatoxin standards for food and feeds would be more effective if the context of local conditions were considered, such as typical crops used as ingredients, capacity to enforce regulations, differentiated aflatoxin contamination levels in food and feeds, regional standards, and societal concerns (food and nutrition security) [50].…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of aflatoxin levels in peanuts at farms and markets in Uganda, Kaya and co-workers [108] reported the presence of aflatoxins at farm level in ≥60% of the peanuts. Results from analysis of raw peanuts, peanut flour, roasted peanuts and peanut butter [84,109] showed a Table 3.…”
Section: Aflatoxin Contamination Of Groundnut and Cashew Nutmentioning
confidence: 99%
“…Improved Spanish groundnut cultivars such as ICGV 91278, ICGV 91283, and ICGV 91284 were selected by ICRISAT showing considerable resistance for aflatoxin-producing fungus (Upadhyaya et al, 2001b). Groundnut accessions ICGs 13,603, 1415, 14,630, 3584, 5195, 6703 and 6888 were recommended for production for their low levels of aflatoxin content (<4 μg kg −1 ) which is far below the regulatory limits for EU (4 μg/kg), most developing countries (10 μg/kg), and the U.S.A. (20 μg/kg) (Magamba et al 2017). Despite breeding progress, aflatoxin levels remain high in commercial groundnut products due to poor regulatory systems and other resource constraints.…”
Section: Progress On Groundnut Variety Development In Ssamentioning
confidence: 99%
“…Despite breeding progress, aflatoxin levels remain high in commercial groundnut products due to poor regulatory systems and other resource constraints. Effective post-and pre-harvest groundnut handling and processing are imperative to minimise aflatoxin contamination along the value chains of the crop (Magamba et al 2017).…”
Section: Progress On Groundnut Variety Development In Ssamentioning
confidence: 99%